PENGARUH INVESTASI, TENAGA KERJA, DAN EKSPOR TERHADAP PDRB SEKTOR INDUSTRI DI KOTA SEMARANG TAHUN 1993-2010 - Karlita, Batari Saraswati; AG, Edy Yusuf (Diponegoro Journal of Economics, 2013)
The objectives of this research is to find how big the influence of investment, labor, and exports values affect in GRDP values of the industrial sector of Semarang Municipality. Based on the results of the regression analysis, the investment variable has a significant influence 0,001 while labor and export variable did not have a significant influence, the cooficient showed 0,465 and 0,654.